The Relationship Between Personal Hygiene, Knowledge Level, and Occupancy Density with the Incidence of Pediculosis Capitis in Children - Abhari, Ghefira Nurringganis; Azmi, Fahriana; Muhajir, Alfian; Mulianingsih, Wiwin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Pediculus humanus capitis lives by drawing blood from the scalp of individuals, leading to discomfort and itching. Inadequate personal cleanliness, notably among learners in Islamic boarding institutions, such as infrequently washing their hair or neglecting general hygiene, may heighten the chances of encountering this issue. This research seeks to explore the connection between personal cleanliness, awareness levels, and room occupancy density with the occurrence of Pediculosis Capitis in junior high students at the Darul Mubarok NW Yasnuhu Pringgabaya Islamic Boarding School. The research utilizes a quantitative strategy employing an analytical observational method along with a cross-sectional study framework. Furthermore, the sampling technique includes a total of 79 children, following specified inclusion and exclusion criteria. The data were evaluated both univariately and bivariately through the Chi-Square test. Findings from the study indicated that the majority of participants were male, mainly in the 7th grade, and most were in their early teenage years. The number of children with pediculosis capitis was higher (62.0%), respondents with poor personal hygiene were higher (54.4%), most respondents still had poor knowledge, and the majority of students lived in crowded rooms (93.7%). The results of the chi-square test revealed a p-value of 0.001 (p < 0.05), suggesting there is an important connection between personal cleanliness and the occurrence of pediculosis capitis. The final statement is that personal cleanliness and awareness levels are strongly linked to the occurrence of pediculosis capitis, while there is no connection between crowding in rooms and the occurrence of pediculosis capitis.